Integrated production scheduling method to reduce fuel costs of hot rolling Processes - Takeru DOAN; Satoshi NAGAHARA; Takafumi CHIDA; Junichi KATSUBE; Tooru ADACHI; Satoru MITA (Nihon Kikai Gakkai ronbunshu, 2021)
In order to minimize the fuel cost for heating steel ingots in hot rolling process, it is important to plan (1) batch formation to increase filling rate in furnaces and (2) work schedule to reduce stagnation of ingots in furnaces. A low filling rate increases fuel cost per ingot, and stagnation causes additional fuel cost to keep ingot’s temperature. However, the conventional divide-and-conquer methods cannot realize both high filling rate and small stagnation because of planning batch formation and work schedule sequentially. Therefore, we developed a new scheduling method that plans batch formation and work schedule simultaneously by creating multiple candidates of batch. As a result of the computational experiment, the development method reduced 12.3% fuel cost per production compared to the conventional method. The developed method has been applied to actual hot rolling line and reduced the fuel cost by 8%.